Clinical effect of immunomodulatory therapy in periodontitis: a systematic review and meta-analysis - Zhang, Yubing; Qin, Xu; Yang, Jiexuan; Rogers, Hannah M.; Baban, Babak; Tian, Siwei (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesTo evaluate the clinical effect of immunomodulatory therapy in periodontitis, and to identify the possible key inflammatory factors to intervene to modulate the immune status and improve periodontal conditions.Materials and methodsAn electronic search was conducted for human-based studies published until October 2025 on MEDLINE (PubMed), ISI Web of Science, EMBASE, and the Cochrane Database. Randomized controlled trials (RCTs) comparing the effectiveness of immunotherapy and placebo were included. We also compared cytokine levels between the immunotherapy group and the non-immunotherapy group to identify the specific inflammatory mediators influenced by immunotherapy but not by SRP (Scaling and Root Planning). Meta-analyses with fixed and random effects models were performed. Risk of bias assessment was also performed for randomized controlled trials.ResultsOf the 34 articles selected, 22 were included in the meta-analysis (n = 991). It was found that immunomodulatory therapy improved clinical attachment level (CAL), bleeding from probing (BOP), and depth of probing (PD) in patients with periodontitis. A three-group meta-analysis showed that immunotherapy affected periodontal disease progression by modulating local immune factors IL-1β, IL-17, IL-6, IL-8 and TNF-α, thus providing a potential statistically significant benefit.ConclusionImmunotherapy influenced periodontal disease progression through the modulation of local immune factors. The data support the use of immunotherapy as an adjunct to conventional mechanical therapy. Further investigations are warranted to elucidate sources of heterogeneity of the results and examine the potentiality of using inflammatory cytokines as novel targets for the treatment of periodontal disease.